A XANES STUDY OF CU SPECIATION IN HIGH-TEMPERATURE BRINES USING SYNTHETIC FLUID INCLUSIONS - Berry A.J.; Hack A.C.; Mavrogenes J.A.; Newville M.; Sutton S.R. (My University, 2006)
Cu K-edge X-ray absorption near edge structure (XANES) spectra were recorded from individual synthetic brine fluid inclusions as a function of temperature up to 500 °C. The inclusions serve as sample cells for high-temperature spectroscopic studies of aqueous Cu-Cl speciation. Cu+ and Cu2+ can both be identified from characteristic pre-edge features. Mixed oxidation states can be deconvoluted using linear combinations of Cu+ and Cu2+ spectra. This work illustrates how complex Cu XANES spectra can be interpreted successfully. Cu2+ is the stable oxidation state in solution at room temperature and Cu+ at high temperatures. The change in oxidation state with temperature was completely reversible. Cu+ was found to occur exclusively as the linear species [CuCl2]- in solutions containing KCl with Cu:Cl ratios up to 1:6. In the absence of K+, there is evidence for higher order coordination of Cu+, in particular the tetrahedral complex [CuCl4]3-. The importance of such complexes in natural ore-forming fluids is yet to be determined, but may explain the vapor-phase partitioning of Cu as a Cl complex from a Cl-rich brine.
Keywords: CU IN HIGH-TEMPERATURE BRINES; EXPERIMENTAL PETROLOGY; FLUID PHASE; HIGH-TEMPERATURE STUDIES; SYNTHETIC FLUID INCLUSIONS; XANES OF FLUID INCLUSIONS; XAS (XAFS, XANES)